Peningkatan Kemampuan Mahasiswa Membuat Proposal Penelitian Melalui Model Pembelajaran Langsung (Studi pada Program Studi Pendidikan Agama Islam STAIN Parepare) - Sri Mulianah; Ali Rahman (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
This study entitled "Improvement of Student Makes Proposal Through Direct Learning Model (Studies in Islamic Religious Education Program STAIN Pare Pare).". This study aims to determine the increase in the ability of students to make a proposal after learning directly in the course of research methods in education 2 STAIN Parepare. This research method is a method of classroom action research conducted to improve the ability of students to make a research proposal through direct learning model. The process of implementation of the measures implemented in stages until the research is successful. The procedure initiated actions of (1) the action plan, (2) implementation of the action, (3) observation, and (4) reflection. Results of the research study showed that increased significantly on the ability of students to make a research proposal through direct learning model with the average rate of success of 91, 57%. There is an increased ability of the students carry out the task of making a research proposal on the parts of the research proposal. Part Chapter I Introduction, 90.36% first cycle, the second cycle increased 91.57, and third cycle maximum 91 attempts, 57%. The ability of the students carry out the task of making a research proposal in Chapter II Review of Theory / Reader, the first cycle of 50, 6%, the second cycle has increased significantly 90, 36%, and the third cycle is also increased to 91, 57%. The ability of the students carry out the task of making a research proposal in Chapter III Methods, the first cycle of 18, 07%, the second cycle, a significant increase 83, 13%, and third cycles be better 91, 57%.